Perbandingan Watermarking Citra dengan Alihragam Wavelet dan Discrete Cosine Transform - Dwiandiyanta, B. Yudi (Universitas Atma Jaya Yogyakarta, 2011)
Abstract. Comparison of Image Watermarking with the Wavelet Variety Packs and Discrete Cosine Transform. Watermarking is one method of copyright protection to combat the spread of the work of someone illegally. In this study, we compare watermarking algorithm in wavelet region and Discrete Cosine Transform (DCT). Color image is used as the host image, while the watermark image is used as a binary image of size 1 / 16 image of the host. Embedding process is based on Human Visual System (HVS), so hopefully gained an invisible watermark (invisible watermark). Embedding process performed by the additive algorithm. In both variety packs developed, the watermark is inserted in the high frequency components of the image. Wavelet used is the wavelet db4. DCT 4x4 blocks are used, which is expected to reduce the computational load. Tests showed that the two watermarking algorithms are generally resistant to granting noise, geometric image operations and image processing operations. Watermarking algorithm that was developed less defend against attacks-down pass filter and median filter, but has a very good performance against an attack-pass filter above. Keywords: image watermarking, wavelet, Discrete Cosine Transform (DCT), Human Visual System (HVS)Â Abstrak. Watermarking merupakan salah satu metode proteksi hak cipta untuk menanggulangi penyebaran karya seseorang secara ilegal. Pada penelitian ini dilakukan perbandingan algoritma watermarking pada kawasan wavelet dan Discrete Cosine Transform (DCT). Citra warna digunakan sebagai citra host, sedangkan sebagai citra watermark digunakan citra biner berukuran 1/16 citra host. Proses embedding dilakukan berdasarkan Human Visual System (HVS), sehingga diharapkan diperoleh watermark yang tidak kelihatan (invisible watermark). Proses embedding dilakukan dengan algoritma aditif. Pada kedua alihragam yang dikembangkan, watermark disisipkan pada komponen frekuensi tinggi citra. Wavelet yang digunakan adalah wavelet db4. Sedangkan alihragam DCT yang digunakan adalah operasi blok 4x4, yang diharapkan dapat mengurangi beban komputasi. Pengujian menunjukkan bahwa kedua algoritma watermarking secara umum tahan terhadap pemberian derau, operasi geometris citra dan operasi-operasi pengolahan citra. Algoritma watermarking yang dikembangkan kurang bertahan terhadap serangan-serangan tapis lolos-bawah dan tapis median, namun mempunyai unjuk kerja yang sangat baik terhadap serangan tapis lolos-atas.Â Kata Kunci: watermarking citra, wavelet, Discrete Cosine Transform (DCT), Human Visual System (HVS)